2020
DOI: 10.1037/ser0000290
|View full text |Cite
|
Sign up to set email alerts
|

Military sexual trauma survivors’ perceptions of Veterans Health Administration care: A qualitative examination.

Abstract: Although the Veterans Health Administration (VHA) provides free health care related to military sexual trauma (MST), many veterans forgo or delay such care, underscoring the need for research aimed at understanding MST survivors' perceptions and concerns regarding VHA care. This study employed a qualitative phenomenological approach to describe MST survivors': (a) perceptions of VHA care, (b) concerns about VHA care, and (c) suggestions for how VHA can facilitate recovery from MST. Fifty veterans (32 women, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 29 publications
(39 reference statements)
2
52
0
1
Order By: Relevance
“…Subsequent questions sought to elicit participants’ perceptions of the effects of MST on their lives; these questions began broadly and then inquired about effects on different domains (e.g., how participants viewed themselves, their emotions, their attitudes toward the military, ways in which they coped, their bodies, and sleep). Additional questions queried the experience of MST in relation to suicidality and perceptions of VHA care but were beyond the scope of the present aims and thus were not analyzed for this article (Monteith, Bahraini, Gerber, et al, in press). Cisgender female psychologists or master’s-level counselors conducted all interviews, which were audio recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent questions sought to elicit participants’ perceptions of the effects of MST on their lives; these questions began broadly and then inquired about effects on different domains (e.g., how participants viewed themselves, their emotions, their attitudes toward the military, ways in which they coped, their bodies, and sleep). Additional questions queried the experience of MST in relation to suicidality and perceptions of VHA care but were beyond the scope of the present aims and thus were not analyzed for this article (Monteith, Bahraini, Gerber, et al, in press). Cisgender female psychologists or master’s-level counselors conducted all interviews, which were audio recorded.…”
Section: Methodsmentioning
confidence: 99%
“…At both 2-and 4-month follow-ups, women in the SHE group had higher rates of treatment initiation and utilization. Findings have important clinical significance for the serious public health concern of sexual assault against women, which is associated with psychiatric disorders 2 , low utilization of mental health treatment [4][5][6][7] , and increased risk for re-victimization 3 . The SHE program provides a promising tool for engaging women in mental health treatment that overcomes several provider and patient barriers and has the potential to have a high reach.…”
Section: Discussionmentioning
confidence: 99%
“…An unfortunate phenomenon among sexual assault survivors is the repeat experience of gender-based violence including intimate partner violence (IPV) 3 . The experience and consequences of sexual assault and the dual experience of sexual assault and IPV are accompanied by stigma and other barriers shown to delay or inhibit mental health treatment seeking when it is needed, including among women veterans [4][5][6][7][8] . Women veterans experience high rates of sexual assault before, during, and after military service 9,10 .…”
mentioning
confidence: 99%
“…Also consistent with findings by Monteith, Bahraini, et al (), our results demonstrated that female service members and veterans who described institutional betrayal reported more severe symptoms of depression. In recent qualitative research with male MST survivors who had served in a variety of service eras, participants described feeling betrayed by the military, in part, due to the lack of institutional policies to protect them (Monteith, Bahraini, et al, ). MST survivors may feel hopeless, powerless, and unsupported if they believe that a military institution failed to protect them from being sexual assaulted or sexually harassed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, those who encountered institutional betrayal following MST may harbor negative perceptions toward the military organization and their time in service, which could negatively impact recovery and reintegration into civilian life among those separated from the military. Researchers have proposed that institutional betrayal following MST may deter help‐seeking for MST‐related sequelae from VHA or other institutions deemed to be affiliated with the institution in which sexual assault or sexual harassment occurred (Holliday & Monteith, ; Monteith, Bahraini, et al, ; Reinhardt, Smith, & Freyd, ), an important area of research warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%